2020
DOI: 10.1097/acm.0000000000002997
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Analysis of Entrustment-Derived Workplace-Based Assessments

Abstract: Purpose To examine the reliability and attributable facets of variance within an entrustment-derived workplace-based assessment system. Method Faculty at the University of Cincinnati Medical Center internal medicine residency program (a 3-year program) assessed residents using discrete workplace-based skills called observable practice activities (OPAs) rated on an entrustment scale. Ratings from July 2012 to December 2016 were analyzed using application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
2
29
1
Order By: Relevance
“…Competency-based medical education (CBME) has brought increased focus on learner abilities, often measured with WBAs. While this method has the advantage of assessing real-world performance, there are several drawbacks including assessors using variable frames of reference 29 leading to suboptimal reliability for high-stakes decisions, [36][37][38] as well as the challenge of ensuring direct learner observation. 39 By reducing reliance on raters, RSQMs greatly reduce challenges of rater bias and supplement direct observation to give insight into resident performance.…”
Section: Discussionmentioning
confidence: 99%
“…Competency-based medical education (CBME) has brought increased focus on learner abilities, often measured with WBAs. While this method has the advantage of assessing real-world performance, there are several drawbacks including assessors using variable frames of reference 29 leading to suboptimal reliability for high-stakes decisions, [36][37][38] as well as the challenge of ensuring direct learner observation. 39 By reducing reliance on raters, RSQMs greatly reduce challenges of rater bias and supplement direct observation to give insight into resident performance.…”
Section: Discussionmentioning
confidence: 99%
“…Dashboards to display these data are set to change color when a z-score is greater than one standard deviation below expected. We have been using this statistical modeling, a type of learning analytics, for several years to account for construct-irrelevant variance and help make sense of educational data [ 26 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The average for the control population was 3795 and 3715 for the study population. We chose the cumulative z‑score to identify our study population because previous findings in our program of assessment have shown higher reliability and it lessened the risk of including residents with temporary struggles [ 26 ]. Twenty-six of these residents were greater than one standard deviation below the mean z‑score (38% female).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 OPAs As a Possible Solution for Assessing Noncognitive Abilities One process with emerging validity evidence for synthesizing disparate assessment elements into meaningful information is the observable practice activity (OPA) system. [35][36][37][38][39] OPAs are discrete work-based assessment elements collected over time and mapped to larger structures, such as milestones, EPAs, or competencies, to create learning trajectories for formative and summative decisions. 35,36 OPAs drill down to observable behaviors that inform the whole and are similar conceptually to nested EPAs.…”
Section: Cbme and Observable Behaviorsmentioning
confidence: 99%